(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Numerous herbal medications have historically been used for their neuroprotective properties. The goal of that study's research was to find out whether female rats suffering from global cerebral ischemia and reperfusion could benefit from an ethanolic extract of the Moringa oleifera flower. All animals underwent a 10-day pretreatment period.Normal control (group I) rats received 10 days of pre-treatment with 1% carboxymethyl cellulose (CMC). Ischemic control (group II), MOE low dosage (group III), MOE high dose (group IV), and standard medicine Quercetin (group V) were pre-treated with 1%CMC 1ml/kg, MOE 200mg/kg, MOFE 400mg/kg, and Quercetin (group V) at 25mg/kg for 10 days respectively. On the ninth day, all behavioural parameters were evaluated. In order to produce reperfusion injury for 24 hours, the clips were detached on the tenth day after the BCCAO-induced ischemia had been inflicted for 30 minutes under anaesthesia with ketamine (50 mg/kg, i.p). The incision was then stitched up using silk sutures.All rats were examined for neuroprotective activity and behaviour measures once the reperfusion period had ended. These parameters included neurological score, EPM for spatial memory, rota-rod, locomotor activity, and hanging wire test.As compared to the ischemic group II, group IV (high dosage) significantly (p<0.01) affected neurological score, Rota-rod, locomotor activity, hanging wire test, and transfer delay time (EPM test).Moringa oleifera flower extract(MOE) 400mg/kg exhibited more similar neuroprotectiveefficacyto that of the conventional medication Quercetin 25mg/kg in some ways. The transfer latency depicted in the EPM was substantially more influenced by group IV (400mg/kg) than by group V of quercetin (p<0.01).Numerous oxidative stress and biochemical parameters, such as thiobarbituric acid reactive substances (TBARS), tissue glutathione (GSH), catalase activity, nitric oxide activity, and triphenyltetrazolium chloride (TTC) staining of the brain infarct area, were used to evaluate the neuro-protective potential of various compounds. Catalase activity, superoxide dismutase activity, GSH, TBARS, and NO levels were considerably higher in pre-treatment groups with MOE (200mg per kg and 400mg perkg and quercetin (25mg per kg). The study's findings were based on the histopathological outcome. A study that demonstrated comparable neuro protective efficacy against BCCAO-induced cerebral ischemia in female rats was proof that MOE had neuroprotective activity in comparison to the usual medication Quercetin.